2014
DOI: 10.7860/jcdr/2014/8918.4808
|View full text |Cite
|
Sign up to set email alerts
|

“Is there an Association Between Self- Reported Sleep Duration, Body Mass Index and Waist-Hip Ratio in Young Adults? A Cross-Sectional Pilot Study”

Abstract: Introduction: Sleep is vital for mental and physical health of an individual. Duration of sleep influences the metabolism and regulates body weight.Objective: To assess the cross-sectional association of sleep duration with body mass index (BMI) and waist-hip ratio in Malaysian students. Methods:Eighty-nine Malaysian students of both genders, and with a mean (standard deviation) age of 21.2 (0.9) years were included. Institutional Ethics Committee clearance was obtained prior to the start of study. The subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Another meta-analysis on the effect of exercise on sleep quality, including 66 studies, demonstrated positive effects of the exercise in this field (Kredlow, Capozzoli, Hearon, Calkins, & Otto, 2015). Kamath et al (2014) argued that sleep duration influences on the metabolism and regulates body weight which is consistent with our study, demonstrating the correlation between BMI and sleep quality, sleep latency, sleep disturbance, sleep medications. It was also shown that there was no statistical correlation between sleep duration with BMI and waisthip ratio.…”
Section: Discussionsupporting
confidence: 79%
“…Another meta-analysis on the effect of exercise on sleep quality, including 66 studies, demonstrated positive effects of the exercise in this field (Kredlow, Capozzoli, Hearon, Calkins, & Otto, 2015). Kamath et al (2014) argued that sleep duration influences on the metabolism and regulates body weight which is consistent with our study, demonstrating the correlation between BMI and sleep quality, sleep latency, sleep disturbance, sleep medications. It was also shown that there was no statistical correlation between sleep duration with BMI and waisthip ratio.…”
Section: Discussionsupporting
confidence: 79%
“…Meanwhile, there was an association between sleep quality and skipping classes (p<0.005) and falling asleep in class (p<0.014). The finding was supported by a study done by Ahmed et al (2014), who found that 77.02% of medical students had a high prevalence of poor sleep quality and that this was associated with the academic stressor with 55.9%.…”
Section: Academic Performancementioning
confidence: 60%
“…12 The conclusion drawn from our study goes hand in hand with other researchers who have done similar studies in students pursuing professional courses. 16 The mechanisms to explain this lack of correlation in the adolescent population is still not clear. One probable cause may be due to higher physical activity in this age group to meet the demands of daily classes and shuttling between various classrooms and locations.…”
Section: Discussionmentioning
confidence: 99%
“…One probable cause may be due to higher physical activity in this age group to meet the demands of daily classes and shuttling between various classrooms and locations. 16 Lack of sleep is considered as a stressor which triggers the body to conserve energy resulting in alterations in hormone levels and metabolic rates. The present study did not assess the hormone levels hence future research with a larger group of adolescent population would highlight the cause for this nonmonotonic relationship status of anthropometric parameters and sleep quality in adolescents.…”
Section: Discussionmentioning
confidence: 99%